EFEKTIVITAS PEMBERIAN GEL EKSTRAK ETANOL BUAH BELIMBING WULUH (AVERRHOA BILIMBI LINN) TERHADAP PENYEMBUHAN ULKUS TRAUMATIK MUKOSA ORAL TIKUS WISTAR - Sutanto, Daniel; Molek, Molek; Florenly, Florenly (Politeknik Kesehatan Kemenkes Mamuju, 2025)
Star fruit (Averrhoa bilimbi Linn.) contains flavonoids, tannins, saponins, and triterpenoids that contribute to wound healing. Flavonoids act as antioxidants, tannins reduce inflammation, saponins stimulate collagen formation, and triterpenoids support tissue regeneration. This study aimed to compare the effectiveness of 10% and 20% ethanolic extracts of belimbing wuluh in influencing superoxide dismutase (SOD) and malondialdehyde (MDA) expression as well as fibroblast count in traumatic ulcers. An in vivo experimental design with a post-test only control group was conducted on male Wistar rats for 5 days. Subjects were divided into five groups: standard control, negative control (placebo), positive control (0.1% triamcinolone acetonide), treatment I (10% gel extract), and treatment II (20% gel extract). Kruskal–Wallis analysis showed significant differences among groups (p = 0.0001) for all parameters. The Mann–Whitney post hoc test indicated significant differences between the treatment and control groups, with p = 0.002 in most comparisons. The 20% concentration resulted in higher increases in SOD expression and fibroblast numbers, and greater reductions in MDA levels compared to the 10% concentration. Therefore, the ethanolic gel extract of belimbing wuluh is effective as an antioxidant in promoting the healing of traumatic ulcers, particularly through the activity of flavonoids as free radical scavengers and stimulators of fibroblast proliferation.